Wind energy - Beig, A.; Muyeen, S.M. (2015)
Wind energy is one of the promising renewable energy sources. This chapter presents the wind energy basics, the technology used in harvesting wind energy, and the physics related to wind energy. Brief discussions about the different types of wind energy turbines and generator configurations are presented. The chapter concludes with the advantages and disadvantages of wind energy systems.